Risk factors of Non-fatal Unintentional Home Injuries among Children under 5 Years Old; a Population-Based Study - Nouhjah, Sedigheh; R. Niakan Kalhori, Sharareh; Saki, Azadeh (Archives of Academic Emergency Medicine, 2017)
Introduction: In addition to the annual mortality rate, unintentional home injury may result in temporary or permanent disability and requires medical attention and continuous care in millions of children. This study aimed to explore features and risk factors of these injuries. Methods: In this cross-sectional study, demographic variables and epidemiologic pattern of home injuries among children under 5 years of age were collected via a population-based survey in sevenmain cities of Khuzestan province, southwest Iran, during September 2011 to December 2012. Developing a risk stratification model, independent risk factors of unintentional home injury were determined and put to multivariate logistic regression analysis. Results: 2693 children with the mean age of 27.36 § 15.55 months (1 to 60) were evaluated (50.9% boy). 827 (30.7%) cases had a history of at least one home injury occurrence since birth to study time. The most common injury mechanisms were burning with 291 (38.4%) cases, falling with 214 (28.3%) and poisoning with 66 (8.7%) cases, respectively. The independent risk factors of unintentional home injury were age ¸ 24 month (p<0.001), residency in Ahvaz city (p<0.001), mother’s illiteracy (p<0.014), ethnicity (p<0.001), private housing (p=0.01), birthweight (p<0.001), and being the first child (p=0. 01). Sensitivity, specificity, and area under the ROC curve of the model designed by multivariate analysis were 53.5%, 84.8%, and 0.75 (95% CI: 0.73- 0.77; P < 0.001, figure 1), respectively. Conclusion: According to the findings of this study, 30.7% of the studied children were injured at least once since birth. Burning, falling, poisoning, swallowing objects, choking, and biting were the main home injury mechanisms. Age ¸ 24 months, being the first child, living in a private house, being a resident of Ahvaz city, and having an illiterate mother were found to be risk factors of home injury.